Protective Effect of Proanthocyanidins in Cadmium Induced Neurotoxicity in Mice - Dong, C. (Drug Research, 2015)
Cadmium (Cd) is a potent neurotoxic heavy metal, known to induce oxidative stress and membrane disturbances in brain. Proanthocyanidins (PACs), the most abundant polyphenol class in the human diet, have protective effects on oxidative stress and other metabolic disorders. Based on the cellular protective effect of PACs, we aimed to investigate whether PACs could protect the neuronal cells from Cd-induced excitotoxicity. The experiment was carried out on mice model and also in primary culture of hippocampal neurons isolated from neonatal mice. The Cd-induced changes in acetylcholinesterase (AChE) activity, oxidative stress markers (lipid peroxidation/lipid hydroperoxidation), antioxidant status and Akt phosphorylation were measured in the mice brain with or without PACs treatment. Mice intoxicated with cadmium (5 mg/kg/day) for 4 weeks had significantly (p<0.05) reduced the AChE levels, elevated the levels of oxidative stress markers along with the significant (p<0.05) decrease in the levels of both enzymatic antioxidants and non-enzymatic antioxidants in mice brain tissue. In contrast, administration of PACs (100 mg/kg/day) for 4 weeks in cadmium-intoxicated mice had significantly (p<0.05) protected the cadmium-mediated changes. In addition, PACs treatment in cultured mice hippocampal neurons had protected Cd-induced excitotoxicity by activating Akt phosphorylation, decreasing the caspase-3 level and improving the neuronal cell survival rate up to 24 h. Altogether, our data suggest that PACs plays a crucial role on neuroprotection in combating the cadmium induced oxidative neurotoxicity in mice brain by influencing the activation of AChE/Akt phosphorylation, antioxidant status, controlling the membrane damage (lipid peroxidation) and apoptotic protein caspase-3.
Keywords: cadmium; proanthocyanidins; acetylcholinesterase; oxidative stress